The modified Kocher criteria for septic hip: Does it apply to the knee?. (June 2022) - Bisht, Roy U; Burns, Jessica D; Smith, Casey L; Kang, Paul; Shrader, M Wade; Belthur, Mohan V
Background: Pediatric septic arthritis is a surgical emergency and timely diagnosis prevents serious complications. To differentiate between septic hip and transient synovitis, the predictive value of four original Kocher criteria (fever, inability to bear weight, elevated serum white blood cell count, and elevated erythrocyte sedimentation rate) plus Caird's addition of elevated C-reactive protein have been studied, termed the modified Kocher criteria. These criteria have not been tested extensively on septic knee. This study tested the utility of the modified Kocher criteria in predicting septic knee while validating it for septic hip. Methods: A retrospective chart review was conducted of pediatric patients evaluated at a single institution for irritable hip or knee between 2009 and 2018. Patients who underwent arthrocentesis were included and the modified Kocher criteria were applied to all. Results: One hundred fifty-five patients (96 hips and 59 knees) were identified. One hundred four (67.1%) patients had septic arthritis with 44/59 (74.6%) of knees and 60/96 (62.5%) of hips. The strongest predictors for septic hip and knee were elevated C-reactive protein (odds ratio = 26.9, p  < 0.0001) and refusal to bear weight (odds ratio = 14.5, p  < 0.0001), respectively. For hips, 5/5 criteria produced a 100% positive predictive value for septic arthritis. For knees, the combination of inability to bear weight and elevated C-reactive protein had a positive predictive value of 89.7%. Conclusion: While all five of the modified Kocher criteria are not predictive of pediatric septic knee, the combination of two specific factors (inability to bear weight and elevated C-reactive protein) is strongly predictive. This study validates previous work that the modified Kocher criteria are predictive of septic hip. Level of evidence: level III